Is There a Cumulative Association Between Adverse Childhood Experiences and Intimate Partner Violence in Emerging Adulthood? - Nikulina, Valentina (Journal of interpersonal violence, 2021)
Adverse childhood experiences (ACEs) have been shown to cumulatively predict a range of poor physical and mental health outcomes across adulthood. The cumulative effect of ACEs on intimate partner violence (IPV) in emerging adulthood has not been previously explored. The current study examined the individual and cumulative associations between nine ACEs (emotional abuse, physical abuse, sexual abuse, emotional neglect, physical neglect, witnessing domestic violence, living with a mentally ill, substance abusing, or incarcerated household member) and IPV in a diverse sample of college students (N = 284; Mage = 20.05 years old [SD = 2.5], 32% male, 37% Caucasian, 30% Asian, 33% other, and 27% Hispanic) from an urban, public college in the Northeast of the United States. Participants reported ACEs (measured by the Adverse Childhood Experiences Survey) and IPV perpetration and victimization (measured with the Revised Conflict Tactics Scale–2) of physical and psychological aggression in an online study that took place from 2015 to 2016. Bivariate and multivariate associations between ACEs, cumulative ACEs (assessed by the sum of adverse experiences), and IPV outcomes were assessed, while controlling for demographics and socioeconomic status. No cumulative associations were observed between ACEs and any of the IPV subscales in multivariate regressions, while witnessing domestic violence was significantly associated with perpetration and victimization of physical aggression and injury, and household member incarceration and physical abuse were associated with physical aggression perpetration. Adverse childhood events do not seem to associate cumulatively with IPV in emerging adulthood and the contributions of individual childhood experiences appear to be more relevant for IPV outcomes. Clinical and research implications are discussed.